Monitoring the Complete Life-cycle of a CO2 Storage Reservoir – Demonstration of Applicability of Geoelectrical Imaging. (July 2017) - Schmidt-Hattenberger, Cornelia; Bergmann, Peter; Labitzke, Tim; Pommerencke, Julia; Rippe, Dennis; Wagner, Florian; Wiese, Bernd
Abstract: In this paper, the applicability of deep downhole geoelectrical monitoring for detecting CO2 related signatures is evaluated after a nearly ten year period of CO2 storage at the Ketzin pilot site. Deep downhole electrode arrays have been studied as part of a multi-physical monitoring concept at four CO2 pilot test sites worldwide so far. For these sites, it was considered important to implement the geoelectrical method into the measurement program of tracking the CO2 plume. Analyzing the example of the Ketzin site, it can be seen that during all phases of the CO2 storage reservoir development the resistivity measurements and their corresponding tomographic interpretation contribute in a beneficial manner to the measurement, monitoring and verification (MMV) protocol. The most important impact of a permanent electrode array is its potential as tool for estimating reservoir saturations.